Republic of Fiji : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Fiji. (IMF Staff Country Reports; Country Report ;, 2021)
Fiji has been among the hardest hit by the pandemic-with infection rates at one point among the highest in the world. Despite swift action by the government to close borders, protect the population, and mitigate the worst economic effects, the economic contraction was the worst in Fiji's history. The crisis has come at a heavy social cost, including large-scale layoffs, surging unemployment, and high non-performing loans. Multilateral and bilateral support has been critical in helping Fiji weather the worst of the crisis and has facilitated a strong government response-including rapid acceleration of the government vaccination program underpinning Fiji's reopening to international tourism.